SEPARATION OF WATER AND OIL IN THREE PHASE SEPARATOR WITH COMPUTATIONAL FLUID DYNAMICS APPROACH - Pangeran Aletheia, Samuel
The increasing need for crude oil makes the extraction of crude oil from wells enahnced, so that oil production increases. The use of water as a method of extracting oil from wells causes the oil to contain a large amount of water content, so it must be separated before further processing. Industry uses three-phase separators to separate water and oil, with the aim of separating most of the water before the oil is further processed. However, the manufacture of three-phase separation requires a large amount of money, so it is necessary to design a tool through modeling first. Computational fluid dynamics is a modeling solution for designing accurate threephase separations. The model developed in this study was tested by T-test against real free water knockout at a 95% confidence level, and resulted in a p-value of 0.13. The model that has been obtained is added with internal components such as baffles, coalescer, and diverters to observe their effect on the efficiency of separation. The results of the study show that the diverter provides the most significant increase in efficiency up to 78.04%. Meanwhile, the use of coalescer and baffle provides an increase in the efficiency of separation by 56.82% and 25.10%, respectively. The combination of these three internals provides an increase in separation efficiency of up to 56.82%.